Recent and Historical Gene Flow in Cultivars, Landraces, and a Wild Taxon of Cucurbita pepo in Mexico - Martínez-González, Carmina; Castellanos-Morales, Gabriela; Barrera-Redondo, Josué; Sánchez-de la Vega, Guillermo; Hernández-Rosales, Helena S.; Gasca-Pineda, Jaime; Aguirre-Planter, Erika; Moreno-Letelier, Alejandra; Escalante, Ana E.; Montes-Hernández, Salvador; Lira-Saade, Rafael; Eguiarte, Luis E. (Frontiers in Ecology and Evolution, 2021)
Gene flow among crops and their wild relatives is an active study area in evolutionary biology and agronomy, because genetic exchange between them may impact their evolutionary trajectories and increase the genetic variation of the cultivated lineages. Mexico is a center of diversity for the genus Cucurbita that includes pumpkins, squashes and gourds. Gene flow between domesticated and wild species has been reported as common in Cucurbita; but gene flow among populations of C. pepo ssp. pepo from Mexico and its wild relative has not been studied. We used 2,061 SNPs, derived from tGBS to estimate gene flow among 14 Mexican traditional landraces of C. pepo ssp. pepo, five commercial varieties of C. pepo ssp. pepo and C. pepo ssp. ovifera var. ovifera, and eight individuals of their wild relative C. pepo ssp. fraterna. Pairwise FST values show low to moderate genetic differentiation between the different taxonomic groups of C. pepo; furthermore, the counts of the "AABB" "ABBA" and "BABA" sites are very homogeneous for all the possible arrangements between the lineages, suggesting high levels of gene flow between these varieties or incomplete lineage sorting. Evidence of the use of landraces of Mexico as genetic material for the improvement of commercial varieties was found. The landraces of Mexico are an important source for genetic diversity for C. pepo, diversity that has been preserved both by management practices of small farmers, and by the natural gene flow that exists between the different crop fields of the region.